Peculiarities of extraction of organophosphorus pesticides and its description from the perspective of the principle of additivity of Gibbs energy of distribution - Zayats, Mikhail F.; Leschev, Sergey M.; Furs, Siarhei F.; Zhylko, Vyacheslav V. (Journal of the Belarusian State University. Chemistry, 2017)
The distribution of a number of organophosphorus pesticides of different classes (phosphates, thiophosphates, dithiophosphates, phosphonothioates, phosphonodithioates, phosphoramidates, phosphoramidothioates) was studied at 20 ± 1 °C in extraction systems hexane – water, hexane – ethylene glycol, hexane – acetonitrile, hexane – a mixture of acetonitrile and water and hexane – a mixture of acetonitrile and ethylene glycol. The distribution constants (P) of the pesticides and the values of the functional groups increments (If) between hexane and the polar phase were calculated. The factors that affect these values are discussed. The possibility of prediction of change of the pesticide distribution constants at introduction or replacement of one functional group to another is considered on the basis of the principle of additivity of Gibbs energy of distribution, or the method of group increments. The factors affecting the deviation of the calculated distribution constants of substances from the experimental constants are determined. The influence of the polar phase composition on the change of functional group increments and pesticide distribution constants are considered.